2018
DOI: 10.1128/jvi.00639-18
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus NS5A Protein Promotes the Lysosomal Degradation of Hepatocyte Nuclear Factor 1α via Chaperone-Mediated Autophagy

Abstract: Hepatitis C virus (HCV) infection is closely associated with type 2 diabetes. We reported that HCV infection induces the lysosomal degradation of hepatocyte nuclear factor 1 alpha (HNF-1α) via interaction with HCV nonstructural protein 5A (NS5A) protein, thereby suppressing GLUT2 gene expression. The molecular mechanisms of selective degradation of HNF-1α caused by NS5A are largely unknown. Chaperone-mediated autophagy (CMA) is a selective lysosomal degradation pathway. Here, we investigated whether CMA is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Gregoire et al showed that autophagy can be activated by ectopic expression of HCV NS3 alone (Table 1) [420]. In addition to NS4B and NS3, expression of the HCV core protein can induce complete autophagy (Table 1) [421,422] and another later study showed that HCV NS5A can trigger autophagy (Table 1) [423,424]. Although these results collectively suggest that HCV can activate autophagy via individual viral proteins, many conclusions were drawn based on the transient expression of viral proteins in cells that are not permissive to complete HCV life cycle, which may have led to large discrepant results.…”
Section: Flavivirus-autophagy Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gregoire et al showed that autophagy can be activated by ectopic expression of HCV NS3 alone (Table 1) [420]. In addition to NS4B and NS3, expression of the HCV core protein can induce complete autophagy (Table 1) [421,422] and another later study showed that HCV NS5A can trigger autophagy (Table 1) [423,424]. Although these results collectively suggest that HCV can activate autophagy via individual viral proteins, many conclusions were drawn based on the transient expression of viral proteins in cells that are not permissive to complete HCV life cycle, which may have led to large discrepant results.…”
Section: Flavivirus-autophagy Interactionsmentioning
confidence: 99%
“…On the other hand, HCV-induced CMA was shown to participate in the degradation of IFN-alpha receptor-1 (IFNAR1), which is stimulated by free fatty acid (FFA) (Table 1) [433]. Moreover, Matsui and colleagues recently reported that HCV NS5A can interact with Hsc70, a regulator of CMA, to target hepatocyte nuclear factor 1α (HNF1α) for lysosomal degradation (Table 1) [424]. A recent study implied that HCV-induced IFN-β-inducible SCOTIN recruits NS5A to autolysosomes for degradation, thus restricting HCV replication (Table 1) [434].…”
Section: Flavivirus-autophagy Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In HCV-infected Huh7.5 cells with FFA treatment, IFNAR1 is selectively degraded through interacting with HSC70 and LAMP2A on the lysosome membrane, suggesting that HSC70 inhibits host anti-HCV immunity through mediating autophagy (Ramazan et al, 2015). Another study suggests that HCV NS5A protein interacts with HSC70 and recruits HSC70 to hepatocyte nuclear factor 1 alpha (HNF-α), thereby promoting the CMA-dependent lysosomal degradation of HNF-α and facilitating virus pathogenesis (Matsui et al, 2018). Interestingly, HSC70 can directly participate in cellular host innate immunity by the DNA-dependent protein kinase (DNA-PK) DNA sensing pathway, which induces a robust and broad antiviral response via a non-classical DNA sensing pathway.…”
Section: Hsc70 Correlates With Virus-induced Host-protective Immune Rmentioning
confidence: 99%
“…However, CMA was also reported to be activated by HCV and implicated in the degradation of IFN-alpha receptor-1 (IFNAR1), which is stimulated by FFAs (Table 5) [570]. Another study demonstrated that HCV NS5A interacts with HSC70 to promote the degradation of hepatocyte nuclear factor 1α (HNF1α) (Table 5) [571]. Recently, IFN-β-inducible SCOTIN was shown to recruit HCV NS5A into autolysosomes for degradation, restricting the HCV infection (Table 5) [572].…”
Section: Autophagy: a Friend Or Foe In Liver Diseases?mentioning
confidence: 99%